2016
DOI: 10.1080/02640414.2016.1241418
|View full text |Cite
|
Sign up to set email alerts
|

The role of anthropometric, performance and psychological attributes in predicting selection into an elite development programme in older adolescent rugby league players

Abstract: This study aimed to identify attributes that discriminate selected from non-selected players and predict selection into a rugby league development programme in older adolescent players. Anthropometric, performance and psychological attributes were measured in under-16 (N = 100) and under-18 (N = 60) rugby league players trialling for selection into a development programme with a professional Australian club. Sprint times (P < 0.001), predicted VO (P = 0.002) and push-ups (P = 0.004) were superior in selected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…6 It is possible that rather than body mass per se, it is the rapid increase in body mass required in a short time period ( To the authors' knowledge, no study has explored the differences in anthropometric and physical qualities based on league ranking in rugby league. Our findings concur with those reporting small to large differences between elite and sub-elite players in rugby league 4 and the results of Mohr and Krustrup 16 who reported an 18-20% greater Yo-Yo IR2 distance in top-and middle-ranked teams compared to bottom-ranked teams in semiprofessional soccer. Whilst it is likely that numerous factors influence a team's league ranking, our results suggest that well-developed sprinting ability and rugby-specific intermittent running might be important for success.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…6 It is possible that rather than body mass per se, it is the rapid increase in body mass required in a short time period ( To the authors' knowledge, no study has explored the differences in anthropometric and physical qualities based on league ranking in rugby league. Our findings concur with those reporting small to large differences between elite and sub-elite players in rugby league 4 and the results of Mohr and Krustrup 16 who reported an 18-20% greater Yo-Yo IR2 distance in top-and middle-ranked teams compared to bottom-ranked teams in semiprofessional soccer. Whilst it is likely that numerous factors influence a team's league ranking, our results suggest that well-developed sprinting ability and rugby-specific intermittent running might be important for success.…”
Section: Resultssupporting
confidence: 93%
“…The anthropometric and physical characteristics of rugby league players, including stature, body mass, body composition, speed, strength, power, change of direction speed and intermittent running ability, 1 can influence career progression, 2,3 discriminate between selected and non-selected players, 4,5 differentiate between age categories, 6 influence on-field performance 7,8,9 and have implications for recovery. 7 Furthermore, well-developed physical characteristics might serve to moderate training load and reduce injury risk in team sport athletes.…”
Section: Introductionmentioning
confidence: 99%
“…These findings allow for speculation of the importance of upper-body muscular power in rugby relative to cricket, especially among older U19 rugby participants and also hint at the likelihood of greater development with training in rugby regardless of competitive level. Muscular power is essential in rugby for effective tackles and to push opponents when needed [52].…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Entry onto a TID programme is multidimensional and typically includes physical, technical, tactical, social and perceptual skills 5,6,8 as well as considering maturation. 2,4,8 The anthropometric and physical characteristics of rugby league players appear important and can discriminate between playing standards, [9][10][11] positions, 12,13 those selected and not-selected onto a TID programme 14 and age categories. 15 For example, Tredrea et al 14 observed that those players selected onto a TID programme were faster and more powerful than non-selected players.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,8 The anthropometric and physical characteristics of rugby league players appear important and can discriminate between playing standards, [9][10][11] positions, 12,13 those selected and not-selected onto a TID programme 14 and age categories. 15 For example, Tredrea et al 14 observed that those players selected onto a TID programme were faster and more powerful than non-selected players. Till et al 4 also reported that a combination of anthropometric and physical characteristics accurately discriminated between amateur and professional status in rugby league (sensitivity > 83%).…”
Section: Introductionmentioning
confidence: 99%